2018
DOI: 10.1037/cou0000269
|View full text |Cite
|
Sign up to set email alerts
|

Unmet social support needs among college students: Relations between social support discrepancy and depressive and anxiety symptoms.

Abstract: Social support is a widely studied construct due to its associations with physical and emotional well-being outcomes (Uchino, 2006). However, little research examines the context within which receiving support may be helpful (Picard, Lee, & Hunsley, 1997). Whereas examinations of support adequacy are present in the literature (e.g., Song et al., 2012), limited research considers the difference between support needs and support received when the 2 are separated as distinct constructs. The current study consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 96 publications
3
30
1
1
Order By: Relevance
“…Previous research documents a powerful connection between social support and depressive symptoms in college students. Rankin et al (2018) found social support a more powerful predictor of depressive symptoms in college students than personality traits, attachment traits, social network size, or perceived stress.…”
Section: Discussionmentioning
confidence: 83%
“…Previous research documents a powerful connection between social support and depressive symptoms in college students. Rankin et al (2018) found social support a more powerful predictor of depressive symptoms in college students than personality traits, attachment traits, social network size, or perceived stress.…”
Section: Discussionmentioning
confidence: 83%
“…One of these coping mechanisms is social support. Social support consists of an individual's social resources such as family, friends, and a special person [18,19]. Cobb [20] mentions that social support makes individuals feel respected and valued.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Social support has been reported to have a protective effect on college students' mental health [15]. Furthermore, the inadequate social support may increase the risk of depressive symptoms among college students [16]. Moreover, as an internal psychological resource, hope is closely related to an individual's goals and expectations for the future and can have a positive impact on one's behavior and attitude [17].…”
Section: Introductionmentioning
confidence: 99%